PERTUMBUHAN TANAMAN KRISAN (Crhysantemum) DENGAN BERBAGAI PENAMBAHAN WARNA CAHAYA LAMPU LED SELAMA 30 HARI PADA FASE VEGETATIF - I Kadek Wahyu Wiguna; I Made Anom. S. Wijaya; I Made Nada (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2015)
The objectives of this research were to observe the effect of addition coloured LED light on plant growth of chrysanthemum, and to observe the appropriate color lights that resulted to the best plant growth of chrysanthemum. The experimental design used was Completely Randomized Design (CRD) with one factor. The factor used was LED color lights, consisted of red, yellow, green, blue, and white LED light colors. Data were analyzed using ANOVA, followed by LSD (Least Significance Different) test if the treatment effect was significant. The variables observed that growth variables include: plant height, number of leaf and canopy area. The result showed that addition coloured LED light of positive effect against the growth of chrysanthemum. The addition of coloured LED light increased the plant growth. The red light color gave the best effect against plant growth. It showed by the highest plant height (71.50 cm), the most number of leaf blade (33.00) and the biggest canopy area (478.34 cm2).